Pengaruh Love of Money, Equity Sensitivity, dan Machiavellian Pada Persepsi Etis Mahasiswa Akuntansi - Sari, Ni Luh Putu Widia Ananda; Widanaputra, A.A.G.P (E-Jurnal Akuntansi, 2019)
This study aims to examine the effect of love of money, equity sensitivity, and Machiavellian as individual aspects that influence ethical perception. This research was conducted at Faculty of Economics and Business, Udayana University. The sample in this study is the 2015 accounting non regular program students. The number of samples used is 65 respondents with non probability sampling techniques. The results of the study found that love of money negatively affected the ethical perceptions of accounting students. This means that the higher the love of money, the lower the ethical perception of accounting students. Equity sensitivity has a positive effect on the ethical perceptions of accounting students. This means that the higher the equity sensitivity, the higher the ethical perception of accounting students. Machiavellian has a negative effect on the ethical perceptions of accounting students. This means that the higher Machiavellian, the lower the ethical perception of accounting students. Keywords: Love of money, equity sensitivity, machiavellian, ethical perception.